None for the Road? Stricter Drink Driving Laws and Road Accidents - Marco Francesconi; Jonathan James (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Reducing drink drive limits is generally regarded an effective strategy to save lives on the road. Using several new administrative data sources, we evaluate the effect of a stricter limit introduced in Scotland in 2014. This reduction had no effect on drink driving and road collisions. Estimates from a supply-of-offenses function suggests that the reform did not have much ex-ante scope for sizeable effects. The unavailability of cheaper alternative means of transportation and weak law enforcement seem to have been the main channels behind the lack of an impact. We find no externality on a wide range of domains, from alcohol consumption to criminal activities other than drink driving.
Keywords: I12; I18; D62; K42; 330; driving under the influence; road collisions; health; alcohol; crime